Darmstadt 1992 — the Understory - Steenhuisen, Paul (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2005)
Present at Darmstadt in 1992, this Canadian composer also had several of his works performed, notably by the celebrated violinist Irvine Arditti. He relates his nearly missed encounter with Helmut Lachenmann, and the friendships he made with other Canadian composers and performers. Steenhuisen describes a Darmstadt true to its reputation as arrogant and unhealthily competitive and self-conscious, but also still capable of delivering profoundly inspired, spontaneous, and strong musical moments.